2019
DOI: 10.1177/0963689719854446
|View full text |Cite
|
Sign up to set email alerts
|

Rat Facial Nerve Regeneration with Human Immature Dental Pulp Stem Cells

Abstract: Facial paralysis can result in severe implications for the patients. However, stem cell biology has become an important field in regenerative medicine since the discovery and characterization of mesenchymal stem cells. Our aim was to evaluate the regeneration after facial nerve crush injury and application of human immature dental pulp stem cells (iDPSC). For this study 70 Wistar rats underwent a unilateral facial nerve crush injury and were divided into two groups: Group I (GI): Crushed; Group II (GII): Crush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…Dental MSCs also hold promise for the treatment of facial nerve injury. Recent experimental evidence showed that a novel method to treat crush injury of rats' facial nerve is via a single application of human SHEDs immediately, which could promote a positive local effect on neuroprotection and remyelination in 2 weeks [ 104 ].…”
Section: Dental Msc-based Therapy For Nondental Diseasesmentioning
confidence: 99%
“…Dental MSCs also hold promise for the treatment of facial nerve injury. Recent experimental evidence showed that a novel method to treat crush injury of rats' facial nerve is via a single application of human SHEDs immediately, which could promote a positive local effect on neuroprotection and remyelination in 2 weeks [ 104 ].…”
Section: Dental Msc-based Therapy For Nondental Diseasesmentioning
confidence: 99%
“…Cultured dental pulp-derived cells, which also produce neurotrophic factors such as NGF, BDNF and GDNF, also displayed better therapeutic effects on peripheral nerve regeneration [ 46 , 47 ]. In addition, immature human DPCs have been shown to modulate the effects of proinflammatory cytokines, with increased levels of the anti-inflammatory cytokines IL-6 and IL-10 and reduced levels of proinflammatory factors such as IL-2, IL-4, TNF-α, and IFN-γ [ 48 ]. Immature human DPCs were also shown to affect the migration of Schwann cells into the target tissue and their subsequent proliferation, resulting in the production of several types of trophic factors, including neurotrophins, providing a favorable microenvironment for regeneration [ 49 ].…”
Section: Tissue Engineering With Strategies and Substances In Facial Nerve Regenerationmentioning
confidence: 99%
“…No atual contexto das terapias regenerativas, entre todas as DSC (Figura 1), as que apresentam um maior potencial terapêutico e que são mais utilizadas para fins de pesquisas são células-tronco derivadas da polpa dental de dentes decíduos esfoliados (SHED) ou permanentes (DPSC) (FUJII et al, 2015;SAEZ et al, 2019;TANIKAWA et al, 2020). Estas possuem uma ampla capacidade de se diferenciarem em diversas linhagens celulares e um grande potencial regenerativo, imunomodulador e anti-inflamatório (FUJII et al, 2015;SOARES et al, 2019).…”
Section: Shed E Dpscunclassified